Portrait of British 20th Century Reflected in D. H. Lawrence’s The Virgin and The Gipsy - Ana Widiyanti (Metaphor, 2023)
The purpose of this study is to see the condition of British society in the early 20th Century reflected in D.H. Lawrence’s The Virgin and the Gypsy. The social condition here is related to the reflection of different class-level social life. There are two aims of this study, the first aim is to identify the social condition of England in the early twentieth century depicted in the novel, and the second is to find the social criticism implied through some characterization of the characters in the novel. This research uses a sociological approach with mixed-method analysis. The method used is library research since the thesis deals with a novel. The main data was collected from The Virgin and The Gipsy novel; while the supporting data were collected from internet pages; and other books related to the subject matter. The research finding is that the England social condition was marked by four characteristics, namely: the existence of class distinction, the rise of the middle class, the loss of the nobility's power, and the influence of position on social status. In addition, through the representation of the characters in the novel, the author tries to criticize the way the different classes of people in building a relationship with each other and to criticize the social treatment and judgment toward the lower-class people. During the early twentieth century, the gap between the rich and the poor was obvious and it influences the way people built a relationship in society.